2020
DOI: 10.22146/ajche.51873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gasification Temperature on Synthesis Gas Production and Gasification Performance for Raw and Torrefied Palm Mesocarp Fibre

Abstract: Biomass gasification is widely used for converting solid biomass into synthesis gas for energy applications. Raw biomass is commonly used as feedstock for the gasification process but it usually contains high moisture content and low energy value which lowering synthesis gas production. Thus, torrefaction as a pre-treatment process is necessary in order to upgrade the properties of feedstock for producing more synthesis gas production and improving gasification performance. The objective of this work is to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
3
1
0
Order By: Relevance
“…The behavior is consistent with what Almeida et al [39] found during the gasification experiments at 700-950 • C using olive kernels, waste, and bagasse as feedstock, where a significant increase in H 2 , CO, and CH 4 concentrations was observed up to 850 • C, while CO 2 levels decreased. Similarly, the present results agree with the findings of Halim et al [40] of palm fiber gasification at 650-900 • C, where it was found that with increasing temperature, H 2 concentrations and CO concentrations increased, but CH 4 concentrations decreased. The results of Yahaya et al [41] also agree with the current results, which indicate that increasing the temperature from 700 to 900 • C increased CO and H 2 .…”
Section: Effect Of Temperaturesupporting
confidence: 94%
See 3 more Smart Citations
“…The behavior is consistent with what Almeida et al [39] found during the gasification experiments at 700-950 • C using olive kernels, waste, and bagasse as feedstock, where a significant increase in H 2 , CO, and CH 4 concentrations was observed up to 850 • C, while CO 2 levels decreased. Similarly, the present results agree with the findings of Halim et al [40] of palm fiber gasification at 650-900 • C, where it was found that with increasing temperature, H 2 concentrations and CO concentrations increased, but CH 4 concentrations decreased. The results of Yahaya et al [41] also agree with the current results, which indicate that increasing the temperature from 700 to 900 • C increased CO and H 2 .…”
Section: Effect Of Temperaturesupporting
confidence: 94%
“…This behavior was also observed by Emami et al [44]. Likewise, CH 4 consumption in R 4 and R 5 reduced its concentration at higher temperatures in the gasification of palm fibers [40] and palm kernel shells [41].…”
Section: Effect Of Temperaturesupporting
confidence: 80%
See 2 more Smart Citations